HBR's 10 must reads on leadership lessons from sports. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2018)
The world's elite athletes and coaches achieve high performance through inspiring leadership, strategic choices, and mental toughness. Harvard Business Review has talked to many of them throughout the years to learn how their success can translate to business leadership. If you read nothing else on management lessons from the world of sports, read these 10 articles by athletes, coaches, and experts in the field. We've combed through Harvard Business Review's archive and selected the articles that will best help you drive your performance--whether as a individual contributor or a leader. This book will inspire you to: - Improve your weaknesses, not just your strengths - Hold everyone to high standards--especially your stars - Find meaning in success--and in challenge - Take care of your body for sustained mental performance - Identify the right rivalries to bring out the best in you - Build your team from the bottom up - Understand where the analogy of sports and business doesn't work--
Ferguson's formula / Anita Elberse -- Life's work: an interview with Greg Louganis -- The making of a corporate athlete / Jim Loehr and Tony Schwartz -- The tough work of turning around a team / Bill Parcells -- How an Olympic gold medalist learned to perform under pressure: an interview with Alex Gregory -- Mental preparation secrets of top athletes: an interview with Daniel McGinn / by Sarah Green Carmichael -- SoulCycle's CEO on sustaining growth in a faddish industry / Melanie Whelan -- Life's work: an interview with Kareem Abdul Jabbar -- Major league innovation / Scott Anthony -- Looking past performance in your star talent / Mark de Rond, Adrian Moorhouse, and Matt Rogan -- Life's work: an interview with Mikhail Baryshnikov -- How the best of the best get better and better / Graham Jones -- Life's work: an interview with Joe Girardi -- Why there is an I in team / Mark de Rond -- Life's work: an interview with Andre Agassi -- Why sports are a terrible metaphor for business / Bill Taylor.
Includes bibliographical references and index.
Keywords: Leadership; Success in business; Athletes -- Psychology